Movement Analysis of Two Hand Backhand Techniques in Unimed Tennis Field Community Athlets 2021 - Mahmuddin Mahmuddin; Ade Riana Br. Ginting; Muhammad Faisal Ansari Nasution (UNIB Press, 2022)
The aim is to analyze the two handed backhand motion of the athletes of the Unimed Tennis Community in 2021.The research was carried out at the Medan State University Tennis Court (UNIMED) Jln. William Iskandar Pasar V Medan Estate. Data collection was carried out on October 25, 2021. The number of samples in this study amounted to 3 people. This research is a kind of quantitative approach research (non-experimental) by analyzing the motion of the two-handed backhand technique between athletes who are used as comparisons with international athletes as samples using the Dartfish teampro 5.5 software.The percentage of successful movements analyzed using darfish software Two-handed backhand technique, the position of the prefix movement is Very Good (30%), Good (26.66%), Less (40%), Very Poor (6.66%). The position of the implementation movement is Very Good (14.81%), Good (25.92%), Poor (11.11%), Very Less (48.14%). Position of follow up Very Good (12.5), Good (41.66%), Poor (16.66%), Very Less (29.16%).